Power factor correction in a voltage source converter - Law, Jacky (2014)
Advancement in power electronics has led to the development of power converters. These converters not only control the power flow, but also improve power quality. The voltage source converter is one such converter which has the ability to control the power factor and can provide bi-directional power flow, and constant dc voltage. It has replaced the use of passive filters for some power quality problems. Within the voltage source converter itself, it is necessary to introduce some form of power factor correction to reduce the harmonic distortion present and also to improve the quality of power transmitted. The use of these voltage source converters has slowly replaced the use of passive filters over the years, due to some power quality problems. Thus in this project, we will look into how we will be able to correct the power factor in the single phase half-wave rectifier as the voltage source converter.